Ketertarikan Interpersonal dalam Bertemu, Menyukai, dan Membina Hubungan : Studi Kasus Komunikasi Interpersonal pada Pasangan Suami Istri dalam Menghadapi Permasalahan Rumah Tangga - Ainul Mardiyah; Ahmad Arief; Faris Hibatullah Siregar; Naufal Said Arif (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
This study explores the role of interpersonal communication in the development of marital relationships, particularly when facing household challenges such as suspicion, dishonesty, and lack of emotional support. Using a case study approach, this research analyzes communication patterns, the impact of communication problems on interpersonal attraction, their effects on the process of building a marital relationship, and effective communication strategies for repairing, strengthening, and maintaining the relationship between husband and wife. The findings reveal that open communication, empathy, and emotional support are key factors in enhancing harmony and attraction in marital relationships. Conversely, closed communication patterns, negative dominance, and a lack of empathy and honesty increase the risk of conflict and reduce relationship quality. This paper also identifies effective communication strategies that couples can apply to nurture their relationships, such as improving openness, honesty, and mutual emotional support. These findings are expected to serve as a reference for maintaining harmonious marriages amid the challenges of modern life.